Blue Dynamite: a narrative by John Millett - Perkins, Elizabeth (LiNQ (Literature in North Queensland), 2016)
John Millett, Blue Dynamite: a narrative. Poetry Australia Number 106, 1986. South Head Press, Berrima, NSW. 100 pp. Annual Subscription $27.00.